Utilization of palm oil fuel ash (POFA) as silica source of Ni/SBA-15 for CO2 reforming of CH4 - Nornasuha, Abdullah (2019)
Carbon dioxide (CO2) and methane (CH4) are the major greenhouse gases (GHGs) with 81% and 10 %, respectively, leading to global warming. CO2 reforming of CH4 is a promising route to convert CO2 and CH4 to synthesis gas. Production of synthesis gas by CO2 reforming of CH4 over Ni-based catalyst has been attracted extensive attention worldwide due to its good catalytic activity, low cost, and readily available. However, Ni-based catalyst faces a serious drawback in catalyst surface deactivation by coke formation. Selection of suitable support material was found to be an effective way to reduce the coke formation on catalyst surfaces. In this study, SBA-15 has been chosen as support material due to its interesting textural properties. SBA-15 can be synthesized using templates and variety of silica sources such as tetraethyl ortosilicate and sodium silicate. However, these types of silica precursors are non-eco-friendly and high cost. Therefore, the utilization of palm oil fuel ash (POFA) waste material as an alternative silica source would minimize the cost of SBA-15 production. The preparation of POFA sodium silicate (POFA-Na2SiO3) was done via sodium hydroxide (NaOH) fusion method by investigating several parameters including NaOH/POFA mass ratio, fusion temperature and H2O/NaOH-fused POFA mass ratio. The optimum condition was achieved at NaOH/POFA mass ratio of 2:1, fusion temperature of 550oC, and H2O/NaOH-fused POFA mass ratio of 4:1, with maximum silica content of 40570 ppm. The yield of SiO2 from POFA was 35%. The successful synthesized of SBA-15 was proved by the results of XRD low angle, N2 adsorption-desorption isotherm, and TEM image, corresponding to the SBA-15 mesostructure characteristic. 3wt % of Ni was loaded on the synthesized SBA-15 using various preparation method including conventional impregnation (Ni/SBA-15(IM)), rotary evaporator-assisted impregnation (Ni/SBA-15(RE)), shaker-assisted impregnation (Ni/SBA-15(SH)) and ultrasonic-assisted impregnation (Ni/SBA-15(US)). CO2 reforming of CH4 (CRM) were investigated in a stainless steel fixed bed reactor at 800°C, atmospheric pressure and CO2/CH4 feed composition =1/1. The highest catalytic performance was achieved over Ni/SBA-15(US) with 81 % of CO2 conversion and 90 % of CH4 conversion. This is due to the well Ni distribution on the catalyst surfaces with some of the Ni were located inside the SBA-15 framework, stronger Ni-O-Si interaction, and higher catalyst basicity. Lowest formation of graphite carbon on Ni/SBA-15(US) was correlated to the well dispersion of smaller Ni particles that able to suppress the coke formation. The existence of ultrasonic irradiation offers a cavitation effect to destroy the soft agglomeration of Ni particles and thus lead to a better Ni distribution than conventional impregnation (IM), rotary evaporator-assisted impregnation (RE), and shaker-assisted impregnation (SH) methods. This study provides an idea in preparing a better properties of Ni/SBA-15 catalyst to enhance the activity and stability of CO2 reforming of CH4.